(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the methods of developing endurance physical qualities of athletes on the example of Uzbek martial art (Uzbek jang san’ati, kurash, belbogli kurash). The research studied the system of exercises aimed at developing types of endurance – general and special endurance, load parameters and performance indicators. It was found that in the experimental group trained according to a specially developed methodology, endurance indicators significantly improved compared to the control group. The research results serve to improve the physical training of athletes engaged in Uzbek types of martial arts.